Undifferentiated Pleomorphic Sarcoma of the Duodenal Papilla: A Rare Case and Worth Discussing History - Wang, Jianlong; Liu, Bin; Hou, Jiachao; Li, Tao (Frontiers in Surgery, 2022)
Background Undifferentiated pleomorphic sarcoma (UPS) is a malignant tumor that originates in the mesenchymal tissue and is common in the extremities and retroperitoneum. Primary UPS of the duodenal papilla is rare and a distinct clinical entity. Case presentation In this report, a 48-year-old Chinese man was admitted to our hospital with symptoms of melena. The patient underwent choledochectomy and choledochaljejunostomy for obstructive jaundice 8 years before admission. Endoscopic examination after admission confirmed a mass located at the duodenal papilla. Then, the duodenal papilla and tumor resection were performed, and the histopathology report confirmed the diagnosis of UPS. The patient refused further treatment and died 2 months later due to local recurrence and intrahepatic metastasis. Conclusions It is rare that the mass in the duodenal papilla is diagnosed as UPS. The unpredicted behavior of these tumors warrants a careful plan considering their indolent nature and possible recurrence and metastasis. The prognosis was poor despite the early complete resection.